Level of physical dependence and incidence of pressure ulcers in older patients who belong to PADOMI of hospital III Essalud, Juliaca, Perú - Pari Parillo, Nasia Meliza (2019)
Objetives: The objective was to determine the relationship between physical dependence level andthe incidence of pressure ulcers in elderly patients belonging to PADOMI of Hospital III EsSalud,Juliaca - 2017. Materials and Methods: In a cross - sectional, descriptive and correlational design,the population was constituted by 201 Patients belonging to the Home Care Program, the samplingwas non-probabilistic for convenience with a sample of 51 elderly patients. The instruments used werethe Barthel Index and the Norton Scale. Results: The results indicate that 29.4% of the elderly patientspresent a moderate level of dependence, in the incidence of pressure ulcers, 56.9% of the elderlypatients presented low risk. Finding a statistical correlation (r =, 971) and significant (p <0.00) amongthe study variables. Conclusions: the greater the development of physical independence the lowerthe incidence of pressure ulcers.